ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP INTEGRITAS LAPORAN KEUANGAN - Ustman, Ustman Ustman; Febbiyanti, Lia Dwi (Aktiva : Jurnal Akuntansi dan Investasi, 2023)
Financial reports are a source of information in the form of notes containing financial data of a company for a certain period. Submission or disclosure of the company's financial statements, must be presented with high integrity so that it can be used by report users of financial statements in making decisions. This study aims to determine the effect of company size, leverage, financial distress, and IOS (Investment Opportunity Set) on the integrity of financial statements. This type of research is quantitative research. The population of this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. Sampling in this study used a purposive sampling technique with predetermined criteria. Based on the criteria for sampling, a total sample of 31 companies was obtained. The type and source of data used is from secondary data obtained through the official website of the Indonesia Stock Exchange (IDX). The data analysis technique used is multiple regression using the SPSS Version 26 program as a tool. The results show that partially company size and financial distress have no effect on the integrity of financial statements. Meanwhile, leverage and IOS affect the integrity of financial statements. Simultaneously company size, leverage, financial distress, and IOS affect the integrity of financial reports